Effects of chlorine on cells of Vibrio cholerae - Sousa, Oscarina Viana de (2005)
Since the sixth pandemic outbreak of cholera, chlorine had been used as the ¢rst line of defense. The objective of this investigation was to determine the bactericidal concentration of chlorine against Vibrio cholerae in arti¢cially-contaminated samples of shrimps and water. Cells of V. cholerae were exposed to varying concentrations (5^10 ppm) of chlorine in solution for 5 min. Arti¢cially-contaminated shrimp (Xiphoenaeus kroyer) samples were also dipped for 5 min in chlorine solutions (10 ppm).The results strongly indicate that 8 ppm chlorine was e¡ective in killing viable cells from pure cultures. Isolates of this organism were recovered from carapace, head and tail parts of the crustaceans. V. cholerae strains re-isolated from carapace/head samples seemed to be more resistant than those from tail meat when exposed to10 ppm chlorine solution for 5 min